Organizational culture: does it influence the way a company deals with CSR? - Castro-González, Sandra; Bande Videla, Belén (Development and Learning in Organizations, 2019)
Purpose: This paper aims to show how managers model culture for employees to promote corporate social responsibility (CSR) practices. Design/methodology/approach: The proposal begins by highlighting the importance of culture for CSR implementation and then explains the impact of culture on employees. Findings: Currently, many companies carry out activities under the CSR umbrella, but they may do so without considering whether their company’s context is ideal for such initiatives. They may also not consider the types of employees composing the workforce or their disposition toward CSR. In these circumstances, organizations may miss out on the added value of CSR practices. Originality/value: The important influence of CSR practices on employees’ attitudes and behaviors at work requires organizations to implement these types of actions. Therefore, the contextual factors that are most likely to aid in developing and maintaining these practices must be acknowledged. This paper seeks to offer a new perspective to managers and human resource managers regarding the implementation of CSR activities.
Keywords: corporate social responsibility (CSR); employee; organizational culture; Scopus